The Role of Mathematics Education in Improving Problem Solving Abilities in the Era of Industrial Revolution 4.0: Indonesia - Djafar, Sri Maryani J.; Mukadam, Aisah; Limpudong, Rena; Laurestabo, Risti; Makwan, Gautam (Edutechnium Journal of Educational Technology, 2024)
The industrial revolution 4.0 brings many aspects of change that need to be addressed as a challenge that must be faced, especially in mathematics education. According to the OECD, in the field of mathematics, around 71% of students do not reach the minimum competency level in mathematics. This means that there are still many Indonesian students who have difficulty dealing with situations that require problem-solving skills using mathematics. This study uses a library approach with data sources derived from several articles and to support this research also conducted searches via the internet and books. After the data is collected, data processing is carried out, then data analysis is carried out using descriptive analysis. Data collection techniques used are primary data and secondary data. The data source comes from several articles, namely the work of Maifit Hendriani, Silfi Melindawati and Afri Mardicko with the title "Mathematical Problem Solving Skills in the Industrial Revolution Era 4.0 Elementary School Students", the work of Fitrie Andayani and Adiska Nadiyah Lathifah with the title "Analysis of Problem Solving Capabilities of Middle School Students in Solving Questions on Social Arithmetic Material", by Ayu Yarmayani with the title "Analysis of Mathematical Problem Solving Ability of Class XI Mipa SMA Negeri 1 Jambi City" as well as other journal articles that support this writing. The role of mathematics in the era of the industrial revolution 4.0 as a foundation of knowledge for the development of modern technology and knowledge is very important to study. Someone who has mathematical ability can study the natural surroundings to develop technology for the welfare of mankind. One of these mathematical abilities is problem-solving ability which allows students to solve a mathematical problem or one related to everyday life. The role of mathematics education in improving problem solving abilities in the era of the industrial revolution 4.0 is very important as in this development we are required to be able to keep up with technological and scientific developments which are growing very quickly while the ability to solve mathematical problems in the era of the industrial revolution 4.0 is said to be inadequate. Providing good mathematics education to each student and providing problem solving training can help students develop problem solving skills.